(untitled) (Salud, Arte y Cuidado, 2025)
Identifying and managing all risk factors associated with gestational diabetes is essential for reducing the complications this disease presents for both mother and infant. Therefore, a preventative approach that considers the pregnant woman’s health history, lifestyle, and context promotes a healthy pregnancy and reduces healthcare costs. Thus, it is crucial that all healthcare professionals adopt a comprehensive approach that promotes activities and strategies prioritizing early detection and preventative intervention, fostering environments and resources that support a healthy lifestyle for mothers and families.